2019
DOI: 10.1186/s13068-019-1574-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of d-lactate from methane in a lactate-tolerant strain of Methylomonas sp. DH-1 generated by adaptive laboratory evolution

Abstract: Background Methane, a main component of natural gas and biogas, has gained much attention as an abundant and low-cost carbon source. Methanotrophs, which can use methane as a sole carbon and energy source, are promising hosts to produce value-added chemicals from methane, but their metabolic engineering is still challenging. In previous attempts to produce lactic acid (LA) from methane, LA production levels were limited in part due to LA toxicity. We solved this problem by generating an LA-tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Tomidokoro et al 7 found the mean central CT obtained in a Japanese population was associated significantly with corneal curvature but not with age. Lee et al 8 also found no significant difference in CT in a sample of Korean with respect to age except for the 20-26 year-old age group. Earlier studies 2,[5][6][9][10][11] and recently Hoffman et al 12 19 reported that African Americans had significantly thinner central CT than Caucasians, Asians, or Hispanics.…”
Section: Introductionmentioning
confidence: 90%
“…Tomidokoro et al 7 found the mean central CT obtained in a Japanese population was associated significantly with corneal curvature but not with age. Lee et al 8 also found no significant difference in CT in a sample of Korean with respect to age except for the 20-26 year-old age group. Earlier studies 2,[5][6][9][10][11] and recently Hoffman et al 12 19 reported that African Americans had significantly thinner central CT than Caucasians, Asians, or Hispanics.…”
Section: Introductionmentioning
confidence: 90%
“…Methylomonas sp. DH-1 can convert methane into various value-added compounds and thus has become a promising platform strain for metabolic engineering 47,49,58 . In genome integration, homologous recombination is commonly used in Methylomonas sp.…”
Section: Data 2)mentioning
confidence: 99%
“…Methylomonas sp. DH-1 has recently been shown to utilize methane as a sole carbon source and is gaining great interest as a platform for metabolic engineering [47][48][49] . However, the metabolic engineering of this methanotroph is challenging due to the lack of genetic manipulation tools, including the absence of artificial plasmids for genetic engineering.…”
mentioning
confidence: 99%
“…Adaptive laboratory evolution (ALE) is an important strategy to improve the fitness of microorganisms through selected environmental conditions and was widely used in metabolic engineering ( Papapetridis et al., 2018 ; Lee et al., 2016 ; Choe et al., 2019 ; Phaneuf et al., 2019 ; Gibson et al., 2020 ). Five major application areas of ALE are growth rate optimization ( Sandberg et al., 2014 ; Pfeifer et al., 2017 ), increasing tolerance of the strain ( Qi et al., 2019 ; Wang et al., 2018 ; Pereira et al., 2019 ), increase of substrate utilization ( Kawai et al., 2019 ; Gonzalez-Villanueva et al., 2019 ), increase of product yield/titer ( Gibson et al., 2020 ; Lee et al., 2019 ; Vasconcellos et al., 2019 ) and mechanism discovery ( Tenaillon et al., 2012 ; Kang et al., 2019 ). Fast growth phenotypes of Escherichia coli have been obtained through ALE, and the underlying mechanism has been studied ( LaCroix et al., 2015 ; Long et al., 2017 ; McCloskey et al., 2018 ; Wannier et al., 2018 ; Sandberg et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%